Teacher Performance Improvement Optimization through Teamwork Strengthening, Interpersonal Communication, Adversity Quotient and Work Motivation - Andi Hermawan; Eni Susanti; Briliantina Indrati (UMSU, 2023)
In educational institutions, teachers are a core part of the management element. Teacher Performance Assessment is an assessment of each item of the teacher's main task activities in the context of career development, rank, and position. This assessment is carried out through observation and monitoring. Observation is a process of collecting teacher performance data which is carried out through direct observation of how the teacher works when delivering learning material or guidance in class to students. Observations consist of before observations, during observations and after observations.The implementation of the main task of a teacher cannot be separated from the ability of a teacher in mastering knowledge, skills, and attitudes in carrying out their duties as professional educators. This is a manifestation of the required competencies as regulated in Permendiknas Number 16 of 2007 concerning Academic Qualification Standards and Teacher Competencies. In order to improve teacher performance, research is needed to obtain good information about other variables that can be used to improve teacher performance.The purpose of this study is to make efforts to improve teacher performance by conducting research on the influence between teamwork, interpersonal communication, adversity quotient and work motivation. This study uses the path analysis method (path analysis) to determine the effect between the variables studied and the SITOREM method for indicator analysis in order to obtain optimal solutions in an effort to improve teacher performance. The population of this study were 289 teachers of SMK PGRI in Bogor Regency. From the population, samples were taken using the Slovin formula and a sample of 168 people was obtained.The results of the analysis using the path analysis method show that there is a positive influence between teamwork and teacher performance with a large effect of ?z1 = 0.418 so that strengthening teamwork can improve teacher performance. There is a positive influence between interpersonal communication and teacher performance with a large effect of ?z2 = 0.398 so that the strengthening of interpersonal communication can improve teacher performance. There is a positive influence between adversity quotient and teacher performance with a large effect of ?z3 = 0.445 so that strengthening adversity quotient can improve teacher performance. There is a positive influence between work motivation and teacher performance with a large effect of ?z4 = 0.419 so that strengthening work motivation can improve teacher performance.From the SITOREM analysis, the optimal solution is obtained, namely from the 27 indicators studied there are 14 indicators that are in good condition so that these indicators only need to be maintained or developed, and there are 13 indicators that are still weak and need to be improved. Improvements to indicators that are still weak are complemented by a priority order for their handling. Good indicators are: 1) Ownership, 2) Resilience, 3) Achievement, 4) Job attachment, 5) Good supervision, 6) Adequate rewards, 7) Trust, 8) Harmony, 9) Completeness, 10) Empathy , 11) Openness, 12) Positivity, 13) Work Productivity and 14) Quantity of Work Results Indicators that need to be improved in order of priority for handling are as follows: 1st Control, 2nd Authenticity, 3rd Desire to get appreciation and recognition, 4th Job Guarantee, 5th Desire for power, 6th Accountability, 7th Group Goal Orientation, 8th Coordination, 9th Support, 10th Equality, 11th Quality of Work, 12th Work Effectiveness, 13th Work Efficiency.